Polyphenols and their Mechanism of Action in Allergic Immune ResponseImmune Response - Tünde Juríková; Jiří Mlček; Jiří Sochor; Alžbeta Hegedűsová (Global Journal of Allergy - Peertechz Publications, 2015)
Mini review article deals with the most studied group of chemical compounds - polyphenols - predominantly flavonoids in relation to their allergic immune response. There is clarified and discussed their mechanism of action as well. We emphasized on the strongest inhibitors of allergic reactions - luteolin, fisetin and apigenin, but in the second part the currently studied flavonoids have been summarized as well.